Systemic and Cerebral Vascular Endothelial Growth Factor Levels Increase in Murine Cerebral Malaria along with Increased Calpain and Caspase Activity and Can be Reduced by Erythropoietin Treatment - Hempel, Casper; Hoyer, Nils; Kildemoes, Anna; Jendresen, Charlotte Bille; Kurtzhals, Jørgen Anders Lindholm (Frontiers in Immunology, 2014)
The pathogenesis of cerebral malaria (CM) includes compromised microvascular perfusion, increased inflammation, cytoadhesion, and endothelial activation. These events cause blood–brain barrier disruption and neuropathology and associations with the vascular endothelial growth factor (VEGF) signaling pathway have been shown. We studied this pathway in mice infected with Plasmodium berghei ANKA causing murine CM with or without the use of erythropoietin (EPO) as adjunct therapy. ELISA and western blotting was used for quantification of VEGF and relevant proteins in brain and plasma. CM increased levels of VEGF in brain and plasma and decreased plasma levels of soluble VEGF receptor 2. EPO treatment normalized VEGF receptor 2 levels and reduced brain VEGF levels. Hypoxia-inducible factor (HIF)-1α was significantly upregulated whereas cerebral HIF-2α and EPO levels remained unchanged. Furthermore, we noticed increased caspase-3 and calpain activity in terminally ill mice, as measured by protease-specific cleavage of α-spectrin and p35. In conclusion, we detected increased cerebral and systemic VEGF as well as HIF-1α, which in the brain were reduced to normal in EPO-treated mice. Also caspase and calpain activity was reduced markedly in EPO-treated mice.